Bonding in diborane-metal complexes: a quantum-chemical and experimental study of complexes featuring early and late transition metals - Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2013)
The coordination chemistry of the doubly base-stabilised diborane(4), [HB(hpp)]2 (hpp=1,3,4,6,7,8-hexahydro-2H-pyrimido-[1,2-a]pyrimidinate), was extended by the synthesis of new late transition-metal complexes containing CuI and RhI fragments. A detailed experimental study was conducted and quantum-chemical calculations on the metal-ligand bonding interactions for [HB(hpp)]2 complexes of Group 6, 9, 11 and 12 metals revealed the dominant BHM interactions in the case of early transition-metal fragments, whereas the BBM bonding prevails in the case of the late d-block compounds. These findings support the experimental results as reflected by the IR and NMR spectroscopic parameters of the investigated compounds. DFT calculations on [MeB(hpp)]2 and model reactions between [B2H4⋅2NMe3] and [Rh(μ-Cl)(C2H4)2] showed that the bicyclic guanidinate allows in principle for an oxidative addition of the BB bond. However, the formation of σ-complexes is thermodynamically favoured. The results point to the selective BH or BB bond-activation of diborane compounds by complexation, depending on the chosen transition-metal fragment.
Gesehen am 23.09.2021